The activity of bioactive compounds against several diseases by modulating autophagy - Nurinanda Prisky Qomaladewi; Jae Youl Cho (Institut Teknologi Bandung, 2021)
Several bioactive compounds derived from Indonesia plants, such as xanthorrhizol, gingerol, and pinostrobin are the major compound in a certain plant. They have some pharmacological activities against several diseases, such as inflammation, tumor, and cancer, and modulate other mechanisms. One of them is one of programmed cell death called autophagy. The regulation involves several pathways on upstream and downstream of the autophagy mechanism and affects its activity. Each of the compound has different site of target when it comes to different case of diseases. Here we explained how the bioactive compounds regulate autophagy against several diseases.